CONSTRUÇÃO DE UMA CISTERNA COMO AÇÃO VOLTADA À SUSTENTABILIDADE AMBIENTAL - Soares, Moacir d. L.; Pacheco, Jussiano R.; Corrêa, Geodeli A.; Ferreira, Francesca W.; Mensch, Natália G.; Campos, Tâmela; Kelm, Tamile A.; Brum, Argemiro L.; Specth, Luciano P.; L.T.Squalli, Mara (Salão do Conhecimento, 2013)
Resumo